Dynamics of NK cell subsets following autologous hematopoietic stem cell transplantation in adult oncologic patients - Astarloa-Pando, Gabirel; Sandá, Victor; Amarilla-Irusta, Ainhoa; Lopez-Pardo, Ainara; San Juan, Itxaso; Iturbe-Larrondo, Ainhoa; Pérez-Garay, Raquel; Pérez-Fernández, Silvia; Santos-Zorrozúa, Borja; Manzanares-Martín, Bárbara; Bernardo, Raquel; González, Carmen; et al. (Frontiers in Immunology, 2025)
Early immune reconstitution following autologous hematopoietic stem cell transplantation (autoHSCT) is associated with improved outcome in various cancers. Natural killer (NK) cells are the first lymphocyte subset to recover post-autoHSCT and play a crucial role in antitumor immunity. In this study, we have performed an in-depth characterization of NK cells in adult patients with different hematological malignancies. Our results revealed that, immediately after autoHSCT, NK cells transiently acquired a decidual-like phenotype, displayed a more immature and activated state, and exhibited an upregulation of inhibitory receptors and a downregulation of activating receptors. This decidual-like and activated phenotype was characterized by increased expression of CD56, CD9, CD49a, CD151, CD38 and HLA-DR. Additionally, we assessed plasma cytokine levels and identified associations between cytokine concentrations and NK cell phenotypic changes. In vitro experiments suggested that these phenotype alterations could modulate NK cell function. Finally, in patients with non-Hodgkin lymphoma (NHL), we observed a correlation between NK cell maturation status and progression-free survival. Collectively, our findings provide valuable insights into NK cell dynamics during immune reconstitution following autoHSCT and may inform of strategies for improving patients’ management.